The Influence of Pregnant Women's Knowledge Level on Early Detection of Preeclampsia - Lilik Darwati; Fitriana Ikhtiarinawati Fajrin; Asyaul Wasiah (MBUnivPress, 2024)
The most common causes of maternal death are bleeding, hypertension in pregnancy (preeclampsia and eclampsia), and infection. In fact, hypertension in pregnancy is the second largest cause of maternal death in the world. Objective: . The aim is to analyze the level of knowledge of pregnant women regarding early detection of preeclampsia. The research design used was observational analysis. With a cross-sectional approach, the sample size was 30 people. The sampling technique used was Purposive sampling 14. Using the Chi-Square statistical test. The p-value obtained = 0.000 where the p-value < α 0.05 Conclusion: The results of the analysis found an influence on the level of knowledge of pregnant women regarding early detection of preeclampsia. Make leaflets about preeclampsia in pregnant women which are placed in places that are easy to see, provide education about preeclampsia both verbally and using interesting media.